2014
DOI: 10.3928/01913913-20140429-02
|View full text |Cite
|
Sign up to set email alerts
|

Headache and Refractive Errors in Children

Abstract: Headaches in children usually do not appear to be caused by ophthalmic disease, including refractive error. The prognosis for improvement is favorable, regardless of whether refractive correction is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 10 publications
3
17
0
Order By: Relevance
“…11 However, a different result was obtained in another study where there was no significant association between improvement of headache and correction of refractive error. 10 Majority of the patients with headache and refractive errors in our study had myopia, but greater association with hyperopia 11 and astigmatism 34 has also been found. This may be due to different age groups recruited in different studies.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…11 However, a different result was obtained in another study where there was no significant association between improvement of headache and correction of refractive error. 10 Majority of the patients with headache and refractive errors in our study had myopia, but greater association with hyperopia 11 and astigmatism 34 has also been found. This may be due to different age groups recruited in different studies.…”
Section: Discussionsupporting
confidence: 45%
“…8 Based on clinical experiences and anecdotal evidences from practitioners, the International Headache Society classified it as headache attributed to refractive errors (HARE), 9 although its importance has been frequently questioned. 10,11 In support of the view, it has been suggested that ciliary muscle strain 12 and prolonged contraction of brow, scalp, and neck muscle to improve visibility 13 may cause the headache. The child generally complains of headache when there has been prolonged strain on eye due to reading and relief in absence of such a strain.…”
Section: Introductionmentioning
confidence: 99%
“…11 Roth et al 2008, states that improvement in headache relief is irrespective of RE correction in school children. 13 In the same year, Dotan et al 2014, found that 87.5% of children diagnosed with REs experienced complete resolution from headache after RE correction in 1 month to 3years follow up. 12 Headache is a characteristic of asthenopia accompanied with ocular discomfort, heaviness of eyelids, and brow acheetc.…”
Section: Discussionmentioning
confidence: 97%
“…This hypothesis is under controversy for a long period of time with researches done in different populations with contradictory conclusions. [11][12][13] Several studies have been conducted to find out the relationship between headache and refractive error. Even though the International Headache society (IHS) categorized 'headache associated with refractive error' under secondary headaches, the IHS did not cite any evidence in support of its classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation